Prevention of heatstroke: knowledge, attitude and practices among community population – a cross-sectional study in Jharkhand, India - B., Athira; Kalyani, C. Vasantha; Dhakshayani, T.; Yadav, Mamta; Sharma, Laxmi; Kirti; Rawat, Chitra; Bintu; Monika; Sakshi; Sadhana, K. M. (International Journal of Research in Medical Sciences, 2026)
Background: Heatstroke is a critical and often fatal condition that results from prolonged exposure to high temperatures, exacerbated by climate change. As global temperatures rise, the frequency and intensity of heatwaves have increased, placing populations in heat-vulnerable areas, such as Jharkhand, at significant risk. Despite this, public awareness and preventive practices remain limited. The study aimed to assess the knowledge, attitude and practices regarding prevention of heatstroke and assess the association between knowledge, attitude and practices regarding the prevention of heatstroke with the selected demographic variables of community population. Methods: This cross-sectional study surveyed 405 adults (aged 18-45) attending Out patient department of a tertiary care institute in Jharkhand, India, who were selected by convenient sampling technique. Data was collected through face to face interviews. The survey covered socio-demographic details and knowledge, attitude and practice regarding prevention of heat stroke. Data analysis was performed using statistical package for the social sciences (SPSS) version 26.0, with descriptive and inferential statistics. A significance level (p<0.05) was used for statistical associations. Results: In the current study the majority of participants (26.1%) have good knowledge about the prevention of heatstroke, and they show favorable attitude (61.08 %) towards the preventive measures, and but 9.38% only had good practice during peak heatstroke hours. Knowledge was significantly associated with occupation, educational status, and previous heatstroke experience (p=0.000 for all). Attitude was significantly associated with educational status (p=0.000) and occupation (p=0.029). Practice was significantly associated with occupation (p=0.006). Conclusions: These results underscore the need for targeted public health interventions focusing on occupational and educational profiles to effectively improve heatstroke prevention behaviors in the community.